Thematic Analysis of Management Behaviors of Civilian Nurses in Iran-Iraq War 1980–1988: A Historical Research - Firouzkouhi, Mohammadreza (Iran J Nurs Midwifery Res, 2018)
BACKGROUND: One of the most important roles of nurses in the war was the application of management interventions, which led to provide better services for the wounded soldiers. The purpose of this study was to explore the Management behaviors of civilian nurses in the Iran-Iraq war. MATERIALS AND METHODS: The historical research methodology and thematic analysis using in-depth interviews were applied to gather data. This study was conducted in 2010-2012 in five big cities of Iran, and involved 18 male nurses who were selected by purposeful sampling method. RESULTS: The interviews of the nurses revealed a main category as the management behaviors of the nurses in the war. Six subcategories were obtained, namely call up for the war, establishing emergency teams, managing the therapeutic units, managerial innovation during war operations, teamwork and variety of roles of nurses in the war. CONCLUSIONS: This study demonstrated how the nurses adapted to the harsh a situation without any previous experience on management in crises such as wars and increased medical treatment facilities outcome using management principles.